A simple concept for estimating deadwood carbon in forests. Issue 1 (31st December 2023) - Neumann, Mathias; Echeverria, Sebastian; Hasenauer, Hubert
Abstract: Deadwood in forests is becoming an important topic globally for forest management and carbon markets. While deadwood volume is now routinely assessed by forest inventories and can be even monitored using remote sensing, data about deadwood carbon and density depending on the extent of decay is scarce. We propose a simple concept for estimating deadwood carbon using data from a pilot study in selected coniferous and broadleaf forests covering different climate zones in Austria. We measured deadwood volume and decay classes and calculated deadwood density and carbon fraction from destructive field samples. We found that decay reduces deadwood density significantly, while carbon fraction increases moderately with decay. Partitioning the explained variation confirmed that size and site parameters are more important for explaining deadwood carbon fraction than for deadwood density. These patterns were consistent for coniferous and broadleaf tree species. We also show how to estimate deadwood carbon stocks using standard forest inventory measurements or country statistics, without information on decay classes. We found differences in decay classes of standing versus lying deadwood, and our proposed method allows considering this in large-scale deadwood carbon assessments. We highlight research gaps and missing deadwood information, to provide more accurate carbon assessments of deadwood.